USE OF BIOSYNTHESIZED SILVER NANOPARTICLES OBTAINED FROM MORINGA OLEIFERA EXTRACTS FOR WATER PURIFICATION (FUDMA JOURNAL OF SCIENCES, 2023)
Clean water is essential for human health. Lack of it leads to water borne diseases and environmental pollution. Several techniques that include chlorination, distillation and water sediment filters have been used to purify water however, some of these techniques are expensive, toxic and have many limitations. The use of silver nanoparticles (AgNPs) for water purification has been found to be easier, non-toxic and cost effective. Silver nanoparticles were biosynthesized from Moringa oleifera leaves, stem back, roots and seeds using biomass reaction of aqueous extracts from the different parts of the plants with aqueous solutions of silver nitrate (AgNO3). Spectrometric results showed the presence of nanoparticles in all the extracts to be between the ranges of 350 to 450 wavelengths while the absorbance rate was seen to be within the standard range for silver nanoparticles (1nm – 100nm). This study reveals that Silver nano particles obtained from Moringa oleifera can be used in water purification even though further research on characterization of the particles needs to be done.
Keywords: Biosynthesized, Silver nano particles, Moringa oleifera extracts.